(untitled) (Transactions of the Association of European Schools of Planning, 2020)
The European Spatial Development Perspective (ESDP) (CEC, 1999) was a policy document produced and agreed jointly by EU governments during the 1990s with the support of the European Commission (Faludi and Waterhout, 2002). It was intended as an indicative framework to guide spatially significant public policy making in the EU at all spatial scales from the Community level, to the regional and local levels. A non-binding policy statement, the ESDP sought to guide institutions in the exercise of existing competences which influence spatial development and its application was to be through voluntary co-operation based on the principle of subsidiarity. Integrated application of the ESDP policy options was to be achieved by a reorientation of national spatial development policies and community sectoral policies, at three levels of spatial co-operation - the (European) Community Level; the transnational/national level; and, the regional/local level. In order to achieve this, the ESDP called for ‘horizontal’ co-operation between the authorities responsible for sectoral and spatial policies at each administrative level as well as ‘vertical’ co-operation between the different levels - for example, between the national and local level. The extent of its explicit and implicit application was the subject of academic and policymaker reflection in the years following its adoption (see ESPON, 2006) with its degree of influence being seen as variable across contexts and scales. This special issue brings together a series of papers written in the period between the 20th anniversary of the adoption of the ESDP in Potsdam, Germany in 1999, and the adoption of the new EU Territorial Agenda 2030 (MRSPTDTC, 2020) in December 2020. This seemed an apposite moment to reflect on the legacies of the ESDP and the present and future prospects for European territorial development and urban policy.